A Comparative Analysis of Historical Culinary Recipes Using Topic Modeling and Data Visualization - Maria Teresa Artese; Isabella Gagliardi (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2024)
The proposed method involves analyzing historical culinary recipes through topic modeling and data visualization. It utilizes an unsupervised pipeline, pre-trained language models, and visualization techniques. The method was thoroughly tested on English-language cookbooks and provides information on the evolution of culinary practices.